New onset pancytopenia in adults: a review of underlying pathologies and their associated clinical and laboratory findings. Issue 5 (May 2014) - Devitt, Katherine A.; Lunde, John H.; Lewis, Michael R.
Abstract Pancytopenia is regularly encountered in hematology practice, yet there exist few published assessments of the frequencies of various etiologies, and these frequencies exhibit substantial geographic variation. We reviewed bone marrow specimens from pancytopenic adults to determine the most common etiologies and to identify associations with clinical and laboratory findings. Of 132 patients with no history of hematolymphoid neoplasia, no prior bone marrow study for pancytopenia and no recent cytotoxic chemotherapy, 64% had clonal hematopoietic disorders. Most common were myeloid processes: 26% of patients had acute myeloid leukemia, and 17% had myelodysplasia. Less common were lymphoid neoplasms such as non-Hodgkin lymphoma (6%), hairy cell leukemia (5%) and precursor B acute lymphoblastic leukemia (4%). Among non-clonal cases, the most common specific diagnoses were aplastic anemia (5%), megaloblastic anemia (2%) and human immunodeficiency virus (HIV)-related changes (2%). Clonal diagnoses were associated with more severe cytopenias than non-clonal cases. Circulating nucleated erythroid precursors, immature granulocytes and blasts were seen more frequently in clonal cases. Nearly two-thirds of cases of new onset pancytopenia in adults in our North American practice setting have a clonal etiology, with myeloid neoplasms being most common. Blood counts and peripheral smear findings can provide insights into the likelihood of a clonal etiology.